FAKTOR-FAKTOR YANG MEMPENGARUHI INTENSI UNTUK MELAKUKAN WHISTLEBLOWING INTERNAL (Studi Empiris Pada Satuan Kerja Perangkat Daerah Kabupaten Rokan Hulu) - Sri Husniati; Hardi '; Meilda Wiguna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aimed to know the influence of the Relativism Ethical Orientation, Moral Intensity, Organizational Commitment and Professional Identity to the Intention to carry out an Internal Whistleblowing. The main problem that researchers descriptions are as follows: to see how many significant relationship between the dependent variable to the independent varaibel. This research was conducted on employees SKPD Rokan Hulu. This research was included in the quantitative research. The type of data used in this research is the primary data by source. And then, in data collections sampling was conducted with a purposive sampling method (Sugiyono, 2012: 392) with respondents as many as 104 employees who working in SKPD Rokan Hulu. Data were analyzed using multiple regression with SPSS version 20. The results of this research showed that the Relativism Ethical Orientation have influnce to the intention to carry out an Internal Whistleblowing, moral intensity have influnce to the intention to carry out an Internal Whistleblowing, Organizational Commitment have influnce to the intention to carry out an Internal Whistleblowing, and professional identity have influnce to the intention to carry out an Internal Whistleblowing. So that all the hypotheses presented in this research received.Keywords: Internal whistleblowing, Relativism Ethical Orientation, Moral Intensity, Organizational Commitment, Professional Identity.